2015
DOI: 10.1177/1948550615599827
|View full text |Cite
|
Sign up to set email alerts
|

Out of Work and Out of Luck? Layoffs, System Justification, and Hiring Decisions for People Who Have Been Laid Off

Abstract: Are hiring decisions affected by knowledge that a job applicant was previously laid off? We expected decisional biases to be linked with the motivational tendency to believe that society is fair and outcomes are just and deserved (hereafter, system justifying beliefs [SJBs]). Indeed, hiring decisions were more likely to disadvantage a laid off applicant as SJBs increased both when detailed job application information was reviewed for one laid off applicant (Study 1) and when the applicant was described as one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There is by now a great deal of evidence indicating that people who support politically conservative leaders, parties, policies, and opinions are more likely than others to believe that the “free market” system is not only efficient but just—and that the economic outcomes of the rich and poor are fair and deserved, having emanated from practices that are justified in purely meritocratic terms (Bartels, 2008; Bénabou & Tirole, 2006; Day & Fiske, 2017; Goode, Keefer, & Molina, 2014; Jost, Blount, Pfeffer, & Hunyady, 2003; McCoy & Major, 2007; Monteith, Burns, Rupp, & Mihalec-Adkins, 2016). Conservatives, in other words, exhibit stronger tendencies to engage in economic system justification , in comparison with liberals and moderates.…”
Section: Political Conservatism and System Justificationmentioning
confidence: 99%
“…There is by now a great deal of evidence indicating that people who support politically conservative leaders, parties, policies, and opinions are more likely than others to believe that the “free market” system is not only efficient but just—and that the economic outcomes of the rich and poor are fair and deserved, having emanated from practices that are justified in purely meritocratic terms (Bartels, 2008; Bénabou & Tirole, 2006; Day & Fiske, 2017; Goode, Keefer, & Molina, 2014; Jost, Blount, Pfeffer, & Hunyady, 2003; McCoy & Major, 2007; Monteith, Burns, Rupp, & Mihalec-Adkins, 2016). Conservatives, in other words, exhibit stronger tendencies to engage in economic system justification , in comparison with liberals and moderates.…”
Section: Political Conservatism and System Justificationmentioning
confidence: 99%
“…Initially, system justification theory focused specifically on stereotyping, prejudice, and outgroup favouritism (Jost, ), but it was subsequently expanded to account for a much wider range of outcomes, including appraisals of fairness, justice, legitimacy, deservingness, and entitlement (Brandt & Reyna, ; Jost, ; Jost & Major, ; O'Brien, Major, & Gilbert, ; van der Toorn, Tyler, & Jost, ); attributions and explanations for poverty and inequality (Ali, Ohls, Parker, & Walker, ; Durrheim, Jacobs, & Dixon, ; Godfrey & Wolf, ); spontaneous and deliberate social inferences and judgements about individuals and groups (Jost, Kivetz, Rubini, Guermandi, & Mosso, ; Kay, Jost, & Young, ; Monteith, Burns, Rupp, & Mihalec‐Adkins, ); attitudes and opinions about social, economic, and political issues (Jost, Blount, Pfeffer, & Hunyady, ; Kay et al ., ; Mallett, Huntsinger, & Swim, ; Tan, Liu, Huang, & Zheng, ; van der Toorn, Jost, Packer, Noorbaloochi, & Van Bavel, ); rationalizations for certain sociopolitical outcomes or events (Kay, Jimenez, & Jost, ; Laurin, ); and full‐fledged political and religious ideologies (Jost, Banaji, & Nosek, ; Jost, Glaser, Kruglanski, & Sulloway, ; Jost et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…This contradicts fair and balanced employment relationships and leads to layoff victims suffering from an unjust fate (Dalbert, ). In line with this, a recent study has demonstrated a hiring bias against and, thus, a derogation of layoff victims (Monteith, Burns, Rupp, & Mihalec‐Adkins, ). Beyond that, the perception of prevalent downsizing and a personal past of having been or a personal future of becoming disadvantaged by layoffs should particularly challenge BJW and, therefore, evoke system‐justifying tendencies, especially in those people high in BJW who have a stronger need to rationalize perceived injustice (Dalbert, ; Furnham, ).…”
Section: A System Justification Perspective On Organizational Downsizingmentioning
confidence: 57%